Pattern of disease and type of operation of Surgical Site Infection in obstetrics and gynecology at Dr Soetomo Hospital, Surabaya, Indonesia - Ardi Eko Marsanto; Kuntaman Kuntaman; Hari Paraton; Budi Prasetyo (Majalah Obstetri dan Ginekologi, 2019)
Objectives: to find correlation between risk factors and classification of SSI, the distribution of SSI, and cost in Soetomo Hospital.Materials and Methods: descriptive retrospective observational with correlation analysis between risk factors and SSI classification according to Centers for Disease Control (CDC) definition with univariate analysis. Sub-group descriptive analysis on microbiology result, length of stay (LOS) and cost was also performed. All patients was diagnosed SSI between January 2015 until June 2017.Results: age, referral cases, Body Mass Index, Hemoglobin and Albumin results, types of surgery, types of case are the risk factors we included. Analysis result shows no strong and significance correlation in all risk factors (r 0.053 – 0.447; p 0.072 – 0.971). According to SSI types, the distribution are: superficial (7; 13.2%), deep (26; 49.1%), organ/space (20; 37.7%). Extended-Spectrum Beta-Lactamase (ESBL) was obtained in 19 (14 Obstetrics; 5 Gynecology) from 28 patients with microbiology results. Five deaths occured in ESBL patients (1 Obstetrics; 4 Gynecology; ratio 1 : 11.2). Mean length of stay in Obstetrics and Gynecology was 41.7 and 19.2 days, respectively. Mean cost per day in Obstetrics and Gynecology was 1.2 amd 2.6 million rupiah, respectively.Conclusions: no strong and significant results in all risk factors. Death rate in SSI and malignancy with positive ESBL result are high. Less cost needed for SSI patients, but with longer LOS. Comprehensive approaches are needed to patients at risk of SSI, further study with larger sample are needed.